Graphs with Total Domination Number Double of the Matching Number - Selim Bahadır (Journal of New Theory)
A subset $S$ of vertices of a graph $G$ with no isolated vertex is called a total dominating set of $G$ if each vertex of $G$ has at least one neighbor in the set $S$. The total domination number $γ_t(G)$ of a graph $G$ is the minimum value of the size of a total dominating set of $G$. A subset $M$ of the edges of a graph $G$ is called a matching if no two edges of $M$ have a common vertex. The matching number $ν (G)$ of a graph $G$ is the maximum value of the size of a matching in $G$. It can be observed that $γ_t(G)≤ 2ν(G)$ holds for every graph $G$ with no isolated vertex. This paper studies the graphs satisfying the equality and proves that $γ_t(G)= 2ν(G)$ if and only if every connected component of $G$ is either a triangle or a star.